Exploring electrochemical impedance spectroscopy for the early diagnosis of Mycobacterium tuberculosis using CFP10:ESAT6 protein detection - Ribeiro, Luisa Vogado; Cancino-Bernardi, Juliana; Razzino, Claudia do Amaral; Machado, Thales Rafael; Tuesta, Marco A. M.; Zucolotto, Valtencir (Frontiers in Sensors, 2024)
Tuberculosis (TB) was, until SARS-CoV-2 pandemic, the leading cause of death by a single infectious agent contaminating over 10.6 million people with 1.6 million deaths in 2021 worldwide. Herein, we present a proof-of-principle strategy for detecting the recombinant protein CFP10:ESAT6 using an impedimetric immunosensor, which could aid in the diagnosis of tuberculosis. The immunosensor was developed using indium tin oxide electrodes modified by 3-aminopropyltrimethoxysilane monolayer to covalently immobilize anti-CFP10 antibodies. The protein interaction with the antibody recognition platform was directly monitored and measured by cyclic voltammetry and electrochemical impedance spectroscopy, respectively. After the analytical features optimization, a Langmuir isotherm response from 0.5 ng mL-1 to 50 ng mL-1 of pCFP10:ESAT6, limit of detection of 4.80 ng mL-1 and limit of quantification of 15.97 ng mL-1 were achieved, in a 4-hour assay time. Selectivity tests conducted in the presence of DENV NS1 and SARS-CoV-2 Spike proteins at a concentration of 20 ng mL-1, which is one-tenth of the concentration used to optimize pCFP10, indicate that the immunosensor is selective for pCFP10:ESAT6. Additionally, repeatability and reproducibility tests confirm that the immunosensor is suitable, accurate, and selective for detecting the CFP10:ESAT6 protein. The small sample volume required, and short testing time underscore the remarkable capabilities of this immunosensor and its potential for point-of-care screening and diagnostic aid applications.